Optimal Design and Planning of Biodiesel Supply Chain with Land Competition - Andersen, Federico (2012)
Fil: Andersen, Federico. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química (PLAPIQUI). CONICET; Argentina.